Bribery by a criminal group: problems of qualification - Khassenova, A.R. (Bulletin of the Karaganda University “Law Series”, 2022)
Bribery by a criminal group is one of the most dangerous corruption crimes. The Criminal Code of 2014, for the first time, introduced the concept of a criminal group, which combines various types of group criminal ac-tivity. However, the concept of a criminal group has not received sufficient legal development both in judicial practice and in the domestic criminal law doctrine. A number of responsibility issues for group criminal activ-ity, in particular criminal offenses with a special subject, remain open. This concerns questions about the pos-sibility of participation in a criminal group of persons who do not have the characteristics of a special subject; a minimum number of special subjects that allow the imputation of this qualifying feature; the moment of the end of the crime under the circumstances under consideration, etc. The article is devoted to these issues. The-oretical and applied problems of the qualification of bribe-taking by a criminal group are considered with the involvement of opinions of domestic and foreign scientists. The author’s position on the considered issues is formulated. In particular, the thesis about the need to qualify the actions of all members of the criminal group as co-executors without reference to Art. 28 of the Criminal Code of the Republic of Kazakhstan; the moment of the end of this crime is determined, which is the acceptance of a bribe by any member of the criminal group; the possibility of participation in a criminal group of both special and general subjects is indicated. It is proposed to supplement the normative resolution of the Supreme Court of the Republic of Kazakhstan dat-ed November 27, 2015 No. 8 “On the practice of considering certain corruption crimes” with appropriate ex-planations.